Research on the Hydrological Regime of the Gaoyao Section in the Lower Reaches of Xijiang River by IHA/RVA Method - GAO Minhua (Renmin Zhujiang)
To comprehensively evaluate the changes in the hydrological regime of the Gaoyao section in the lower reaches of the Xijiang River,this study selected the daily average flow data of the Gaoyao Hydrological Station in the lower reaches of the Xijiang River for 1974—2018.The Mann-Kendall method,the Pettitt abrupt change test method,and the cumulative anomaly method were used to analyze the hydrological regime characteristics and abrupt hydrological change points of the Gaoyao section.The indicators of hydrologic alteration/range of variability approach (IHA/RVA) method was employed to comprehensively evaluate the alteration degree of the hydrological index at the Gaoyao Hydrological Station before and after the abrupt change.The results show that from 1974 to 2018,the comprehensive alteration degree of the flow at the Gaoyao Hydrological Station was 37%,and the alteration degree was thus a medium one.The flow generally decreases in the wet season and increases in the dry season.The research results can provide a reference for the proper development of water resources in the lower reaches of the Xijiang River.